2010
DOI: 10.1029/2009ja014516
|View full text |Cite
|
Sign up to set email alerts
|

Storm time observations of electromagnetic ion cyclotron waves at geosynchronous orbit: GOES results

Abstract: [1] Electromagnetic ion cyclotron (EMIC) waves may contribute to ring current ion and radiation belt electron losses, and theoretical studies suggest these processes may be most effective during the main phase of geomagnetic storms. However, ground-based signatures of EMIC waves, Pc1-Pc2 geomagnetic pulsations, are observed more frequently during the recovery phase. We investigate the association of EMIC waves with various storm phases in case and statistical studies of 22 geomagnetic storms over 1996-2003, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
131
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 65 publications
7
131
0
Order By: Relevance
“…Statistically, the proxy and the wave observations agree quite consistently. Both the proxy and the space-based wave observations indicate an abundance of EMIC-wave activity in the storm main phase (Fraser et al 2010). In addition, Blum et al (2009b) found good agreement for some events when GOES and LANL satellites were relatively close to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically, the proxy and the wave observations agree quite consistently. Both the proxy and the space-based wave observations indicate an abundance of EMIC-wave activity in the storm main phase (Fraser et al 2010). In addition, Blum et al (2009b) found good agreement for some events when GOES and LANL satellites were relatively close to each other.…”
Section: Discussionmentioning
confidence: 99%
“…The EMIC source region is typically confined within ≈10 degrees of the geomagnetic equatorial plane, and the Poynting flux at higher latitude is always directed away from the equator, dispelling the long-standing bouncing wave packet model (Loto'aniu et al 2005). EMIC waves are enhanced during magnetic storms (Fraser et al 2010), as anisotropic energetic ring current ions are injected into the inner magnetosphere (Jordanova et al 2001a). EMIC waves can cause rapid scattering and loss for ring current ions (Jordanova et al 2001b) and relativistic electrons above 0.5 MeV (Thorne and Kennel 1971;Lyons and Thorne 1973;Albert 2003;Summers and Thorne 2003;Meredith et al 2003b).…”
Section: Fig 2 Spectrogram Of Waves Observed On Combined Release Andmentioning
confidence: 99%
“…Waves in the band below W He+ are found to be most intense (up to 1000 nT 2 /Hz) statistically during active conditions [Fraser et al, 2010].…”
Section: Introductionmentioning
confidence: 99%